Screening and isolation of heavy metal tolerant bacteria in industrial effluent - Mustapha, Mohamed Umar; Halimoon, Normala (Elsevier, 2015)
Heavy metals tolerant bacteria were isolated from electroplating industry. The activities of electroplating and metal processing industries are regarded as one of the major source of heavy metal pollution. This paper present about the role of microorganisms in heavy metal removal from industrial waste water. In this study 21 bacterial colonies were isolated and tested in the presence of different metals. After screening five best isolates which showed high resistances were selected. The result reveals that all isolates MH1, MH4, MH6 MH15 and MH21 were able to tolerate 50 mg/l of cr, cu, pb and cd. Isolates MH1 and MH21 tolerate 200 mg/l of cadmium while isolate MH4 also showed high degree of resistance to copper. These indicated that the isolates can be used efficiently in removal of heavy metals in contaminated industrial effluents.